2014
DOI: 10.1016/j.gie.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

High and low negative pressure suction techniques in EUS-guided fine-needle tissue acquisition by using 25-gauge needles: a multicenter, prospective, randomized, controlled trial

Abstract: Background: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) has a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 28 publications
(35 reference statements)
1
69
0
1
Order By: Relevance
“…al reported contamination in 13% of samples utilizing standard suction technique. 23,24 In comparison, we found a significant reduction in GI tract contamination once RNP was neutralized (6.7% versus 16.7% in control samples). We utilized rapid on-site cytopathology evaluation, which likely explains our excellent rates of diagnostic cytology yield, similar to multiple studies that have demonstrated higher yield with the use of on-site cytopathology.…”
Section: Discussionmentioning
confidence: 63%
“…al reported contamination in 13% of samples utilizing standard suction technique. 23,24 In comparison, we found a significant reduction in GI tract contamination once RNP was neutralized (6.7% versus 16.7% in control samples). We utilized rapid on-site cytopathology evaluation, which likely explains our excellent rates of diagnostic cytology yield, similar to multiple studies that have demonstrated higher yield with the use of on-site cytopathology.…”
Section: Discussionmentioning
confidence: 63%
“…Our RCTs demonstrated the feasibility of tissue acquisition with 22-or 25-gauge needles using a previously reported scoring system [7,9]. In many patients, an adequate specimen is necessary in order to confirm the tumor histological subtype using immunohistochemical analysis, necessary for selecting a neoadjuvant chemotherapy regimen, especially for tumors that are borderline resectable.…”
mentioning
confidence: 66%
“…Although dedicated instruments make this procedure much easier, samples are easily obtained using only syringes and extension tubes. Although it has been speculated that negative pressure is useful because it holds the tissue against the cutting edge of the needle instead of aspirating tissue into the needle [6], my group reported the utility of high negative pressure (50 mL) compared to customary negative pressure (10 mL) when using 25-gauge needles [7]. We reported significantly higher specimen acquisition rates for adequate histological diagnosis in the high negative pressure group compared to those in the normal negative pressure group (90.0 vs. 72.2 %, P = 0.0003).…”
mentioning
confidence: 99%
“…[596061] Suction may contaminate the sample with blood, clouding cytologic interpretation. EUS-FNA done without suction or by slow-pull technique seems to fare better in terms accuracy and sensitivity of cytologic diagnoses, resulting in only slight blood contamination when aspirating solid lesions.…”
Section: Techniques To Increase Diagnostic Yieldmentioning
confidence: 99%
“…without) suction is superior for tissue acquisition;[59] higher suction pressure seems to yield more tissue. [6163] Biopsy by wet suction technique will also enhance tissue procurement. [64]…”
Section: Techniques To Increase Diagnostic Yieldmentioning
confidence: 99%